A stable and major QTL region on chromosome 2 conditions pod shape in cultivated peanut (Arachis hyopgaea L.) - Sheng-zhong ZHANG; Xiao-hui HU; Fei-fei WANG; Ye CHU; Wei-qiang YANG; Sheng XU; Song WANG; Lan-rong WU; Hao-liang YU; Hua-rong MIAO; Chun FU; Jing CHEN (Journal of Integrative Agriculture)
Peanut pod shape is a heritable trait which affects the market acceptance of in-shell peanut products. In order to determine the genetic control of pod shape, six component traits of pod shape (pod length, pod width, pod length/width ratio, pod roundness, beak degree and constriction degree) were measured using an image-based phenotyping method. A recombinant inbred line (RIL) population consisting of 181 lines was phenotyped across three environments. Continuous distributions and transgressive segregations were demonstrated in all measured traits and environments. Significant correlations were found among most component traits with broad-sense heritability ranging from 0.87 to 0.95. Quantitative trait locus (QTL) analysis yielded 26 additive QTLs explaining 3.79 to 52.37% phenotypic variations. A novel, stable and major QTL region conditioning multiple shape features was detected on chromosome 2, which spans a 10.81-Mb genomic region with 543 putative genes. Bioinformatics analysis revealed several candidate genes in this region. In addition, 73 pairs of epistatic interactions involving 92 loci were identified for six component traits explaining 0.94–6.45% phenotypic variations. These results provide new genetic loci to facilitate genomics-assisted breeding of peanut pod shape.